Design strategies of two-dimensional metal–organic frameworks toward efficient electrocatalysts for N2 reduction: cooperativity of transition metals and organic linkers. Issue 45 (17th November 2021) - Wang, Ran; He, Chaozheng; Chen, Weixing; Fu, Ling; Zhao, Chenxu; Huo, Jinrong; Sun, Chenghua
Abstract : W3 C12 X12 (X = O, S, and Se) were screened as promising NRR electrocatalysts with an ultralow limiting potential. Abstract : Two-dimensional (2D) metal–organic frameworks (MOFs) serve as emerging electrocatalysts due to their high conductivity, chemical tunability, and accessibility of active sites. We herein proposed a series of 2D MOFs with different metal atoms and organic linkers with the formula M3 C12 X12 (M = Cr, Mo, and W; X = NH, O, S, and Se) to design efficient nitrogen reduction reaction (NRR) electrocatalysts. Our theoretical calculations showed that metal atoms in M3 C12 X12 can efficiently capture and activate N2 molecules. Among these candidates, W3 C12 X12 (X = O, S, and Se) show the best NRR performance due to their high activity and selectivity as well as low limiting potential (−0.59 V, −0.14 V, and −0.01 V, respectively). Moreover, we proposed a d-band center descriptor strategy to screen out the high activity and selectivity of M3 C12 X12 for the NRR. Therefore, our work not only demonstrates a class of promising electrocatalysts for the NRR but also provides a strategy for further predicting the catalytic activity of 2D MOFs.